2018
DOI: 10.1016/j.stemcr.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-Renewing Trophoblast Organoids Recapitulate the Developmental Program of the Early Human Placenta

Abstract: SummaryDefective placentation is the underlying cause of various pregnancy complications, such as severe intrauterine growth restriction and preeclampsia. However, studies on human placental development are hampered by the lack of a self-renewing in vitro model that would recapitulate formation of trophoblast progenitors and differentiated subtypes, syncytiotrophoblast (STB) and invasive extravillous trophoblast (EVT), in a 3D orientation. Hence, we established long-term expanding organoid cultures from purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
399
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(425 citation statements)
references
References 62 publications
24
399
0
2
Order By: Relevance
“…Recent optimization of culture conditions for primary human first trimester trophoblasts has led to the development of in vitro trophoblast stem cell lines [28][29][30] . Okae et al 29 defined a TSC medium capable of supporting continued proliferation of primary human cytotrophoblasts and blastocyst-derived trophoblasts when cultured on a collagen type IV matrix.…”
Section: Introduction (Main Text Not Including Abstract Methods Refmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent optimization of culture conditions for primary human first trimester trophoblasts has led to the development of in vitro trophoblast stem cell lines [28][29][30] . Okae et al 29 defined a TSC medium capable of supporting continued proliferation of primary human cytotrophoblasts and blastocyst-derived trophoblasts when cultured on a collagen type IV matrix.…”
Section: Introduction (Main Text Not Including Abstract Methods Refmentioning
confidence: 99%
“…Importantly, under differentiation-specific culture media formulations TSCs could be differentiated to either chorionic gonadotropin (CG)-secreting syncytia or HLA-G positive extravillous trophoblasts (EVTs). In a different approach, Haider et al 28 established a three-dimensional trophoblast organoid model by embedding human cytotrophoblasts, isolated from 6-7 weeks of gestation, into Matrigel and culturing cells in defined medium. The organoid structures formed mononuclear trophoblasts on the outer periphery with an inner layer of CGß expressing multinuclear syncytia.…”
Section: Introduction (Main Text Not Including Abstract Methods Refmentioning
confidence: 99%
“…These improvements will further increase the placental volume of the embryo during post‐implantation . Under 3D in vitro culture conditions, ESCs with self‐assembling properties can develop into natural embryos‐like structures . For example, Harrison et al found that in 3D matrigel, after 96 hours, ESCs can self‐assemble into a cylindrical structure similar to a natural mouse embryo (Figure D).…”
Section: Bioengineered Microenvironment For Early Embryo Culture In Vmentioning
confidence: 99%
“…58 Under 3D in vitro culture conditions, ESCs with self-assembling properties can develop into natural embryos-like structures. 18,34,42,62,63 For example, Harrison et al 41 found that in 3D matrigel, after 96 hours, ESCs can self-assemble into a cylindrical structure similar to a natural mouse embryo ( Figure 3D). The discovery provides a powerful platform for studying the physical and molecular mechanisms of embryonic development.…”
Section: Static Culture Platformsmentioning
confidence: 99%
“…Embryonic and extraembryonic stem cells have been shown to self-organize in 3D culture (45)(46)(47)(48)(49). When ESCs are cultured in a 3D gel supplemented with ECM, they form an apicalbasal polarized shell that eliminates the boundaries of micropattern culture, allowing control of substrate mechanics and chemistry.…”
Section: Self-organization In Embryonic Stem Cellsmentioning
confidence: 99%